Antimicrobial Potential of Fagopyrum esculentum Monech Stem Extract: Phytochemical Characterization and Efficacy Against Drug-Resistant Pathogens - Dubey, Prasant Kumar; Tiwari, Gaurav; Gupta, Naveen; Rajput, Dharmendra Singh; Pounikar, Yogesh (Journal of Neonatal Surgery, 2024)
The escalating crisis of antimicrobial resistance (AMR) demands novel sources of antimicrobial agents. This study investigates the antimicrobial potential of Fagopyrum esculentum (common buckwheat) stem, integrating phytochemical analyses with in vitro antimicrobial assays against a panel of pathogenic microbes. Comprehensive phytochemical screening of the buckwheat stem revealed abundant flavonoids and phenolics; quantitative assays showed high total phenolic (1.52 mg GAE/g) as well as flavonoid (0.14 mg QE/g) contents in extract that is methanolic. Pharmacognostic fluorescence analysis further corroborated the presence of these phytochemicals. Antimicrobial efficacy was evaluated via agar diffusion assays against Staphylococcus aureus, Enterococcus faecalis, Mycobacterium tuberculosis, and a representative Enterobacteriaceae strain (E. coli/Klebsiella). The buckwheat stem extract exhibited dose-dependent inhibition of all tested microbes. Notably, at the highest concentration (3 mg/disc), it produced substantial zones of inhibition against S. aureus ( 15–16 mm) and M. tuberculosis ( 15–18 mm), indicating significant activity comparable to standard antibiotics’ susceptibility thresholds. Moderate activity was observed against Enterococcus (12–15 mm zone at 3 mg) and weaker effects against Gram-negative Enterobacteriaceae (8–12 mm at 3 mg). The extract’s broad-spectrum antibacterial action, especially towards Gram-positive and acid-fast organisms, is attributed to its high polyphenolic content. Potential mechanisms, such as membrane disruption and enzyme inhibition by flavonoids, are discussed. These findings highlight F. esculentum stem as a promising natural source of antimicrobial compounds, meriting further investigation for development into plant-based antimicrobials in the fight against resistant infections.